Effectiveness of Jolly Phonics Program towards Strengthening of Language Literacy: Experimental Case in the Philippines - Maura E Belbes; Marcial M Bandoy; Consorcia S Tan; Alberto D Yazon; Lerma P Buenvinida (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
The Programme for International Student Assessment result of being the lowest in reading comprehension is the main reason that compelled the researcher to conduct the study with the use of the Jolly Phonics program in strengthening language literacy. In addition, at the Division of Cabuyao, there is an issue regarding reading difficulties among Grades 1 to 3 of selected public elementary schools. Despite many strategies being applied, they still find it difficult to read and comprehend. The purpose of this paper is to determine the effectiveness of the Jolly Phonics program in strengthening language literacy and test the hypotheses that there is no significant relationship between the performance of the two groups considering the results of the post-test in language literacy. There were two groups of participants in the study, the experimental group, who utilized the Jolly phonics program, and the comparison group, who were subjected to the Marungko approach. Each approaches utilized thirty (30) pupils from Grades 1 to 3, combining the sum total of 540 participating pupils for three selected elementary schools. The instrument used was the pretest and post-test validated by experts from the City School Division Office. A quasi-experiment research design guided the conduct of the study. A frequency percentage distribution, t-test for independent means, and Analysis of Variance (ANOVA) were among the statistical tools employed in the study. Findings revealed that there was a significant difference in the performance between and among the participating public elementary schools (ES)for Grades 1 to 3. For instance, in Grade 1, it was noted that the performance of Banay – Banay ES was a bit higher than Butong ES and was considerably higher than that of San Isidro ES; In Grade 2, Banay – Banay ES topped in their reading performance compared to other two elementary schools; and In Grade 3, San Isidro ES at this time showed better performance, running over in reading proficiency the other two elementary schools. The action plan was proposed by the researcher of the study to strengthen the language literacy of the learners in the Division of Cabuyao